Brief Report: Association Between Pain, Pulmonary Function, and Respiratory Symptoms in People With HIV. (15th August 2021) - Singhvi, Deepti G.; Nouraie, Mehdi; Kessinger, Cathy; McMahon, Deborah K.; Weinman, Renee; Crothers, Kristina; Huang, Laurence; Bon, Jessica; Morris, Alison; Merlin, Jessica
Abstract : Background: People with HIV (PWH) experience chronic pain and respiratory symptoms, which are closely related in the general population. Pain may affect the impaired pulmonary function seen in PWH beyond its association with HIV alone. Our objective was to investigate the relationship of pain severity to pulmonary function, respiratory symptoms, and sleep disturbance in PWH. Setting: Study sites included the University of Pittsburgh, University of California San Francisco, and University of Washington. Methods: Pain, dyspnea, and sleep were assessed using the Brief Chronic Pain Questionnaire, St. George's Respiratory Questionnaire, and Pittsburgh Sleep Quality Index. Participants performed prebronchodilator and postbronchodilator spirometry and 6-minute walk test. Associations between pain severity, lung function, dyspnea, and sleep were assessed with bivariate and multiple quantile regression analysis adjusted for age, sex, race, body mass index, and smoking status. Results: Of 159 PWH, the median age was 56 years with 30.8% women. Two-thirds experienced pain in the past week, with 40.3% reporting chronic pain. Pain severity was higher with female sex ( P = 0.038), non-White race ( P = 0.005), current smoking ( P = 0.003), and lower CD4 + count ( P = 0.035). In adjusted analysis, higher pain severity was correlated with reduced postbronchodilator forced expiratory volume in 1 second %predicted ( P = 0.008), reduced postbronchodilator forced vital capacity %predicted ( P = 0.019), and chronic obstructive pulmonary disease ( P = 0.032). Greater pain severity was strongly associated with a higher St. George's Respiratory Questionnaire score ( P < 0.001) and sleep disturbance ( P < 0.001). Conclusions: In PWH, pain is common and associated with airflow obstruction, dyspnea, and sleep disturbance. Future studies assessing pain severity and pulmonary function over time could clarify the direction of this association and the impact on quality of life.